Cargo Traffic on the Helsinki-Tallinn Route - Sundberg, Pekka; Posti, Antti; Tapaninen, Ulla (fi=Turun yliopisto|en=University of Turku|, 2011)
The twin-city model has found to increase economical activity and well-being. The similar economical, social and cultural background of Finland and Estonia as well as the EU integration give good preconditions to create a twin-city of Helsinki and Tallinn. The relatively long distance between Helsinki and Tallinn is challenging. Therefore, good transport infrastructure and functioning connections are required to form a twin-city of Helsinki and Tallinn. The connections between these cities can be considered also in broader perspective than only from the viewpoint of the twin-city concept. New markets areas have been emerged in Europe due to collapse of planned economy and integration of Europe. Also the transport routes to the markets are changing. The Hel-sinki-Tallinn sea route can be considered as a fast route to the new markets in the Cen-tral and Eastern Europe. The Helsinki-Tallinn sea route is also a potential route to the Western European markets. This study provides an analysis of transport and cargo flows between Finland and Esto-nia for regional and local planners. The main purpose of the study is to clarify the pre-sent situation of the seaborne cargo flows on the Helsinki-Tallinn route and how the cargo flows will develop in the future. The study focuses on the following thematic enti-ties: the Finnish and Estonian seaborne transport system and cargo flows, the structure and volume of the cargo flows on the Helsinki-Tallinn route, the hinterland cargo flows on the Helsinki-Tallinn route and the transport methods used on the Helsinki-Tallinn route. The study was carried out as a desk research, a statistical analysis and an inter-view study during the spring–autumn 2011. The study reveals that during the period 2002–2010 the volume of the seaborne cargo traffic between Finland and Estonia has increased significantly while the trend of the trade volume between Finland and Estonia has remained nearly constant. This indicates that the route via Estonia is increasingly used in the Finnish foreign trade. Because the ports of Helsinki and Tallinn are the main ports in the cargo traffic between Finland and Estonia, the role of the Helsinki-Tallinn route as a sea leg in the hinterland connections of Finland has increased. The growth of the cargo volume on the Helsinki-Tallinn route was estimated to continue on the annual level of 10 % during the next couple of years. In the long run the growth of the cargo volumes depends on the economical and indus-trial development of the former Eastern European countries. If the IMO’s sulphur regu-lations will come in force, the Helsinki-Tallinn route will become one of the main routes also to the Western European markets, besides of the route via Sweden. The study also shows that the fast and reliable connections year round on the Helsinki-Tallinn route have made it possible for service and logistics companies to reconsider their logistics strategies in a new way in the both side of the Gulf of Finland. Anyway, the ropax concept is seen as the only economical profitable solution on the Helsinki-Tallinn route because cargo and passenger traffic are supporting each other. The trucks (vehicle combinations) will remain the main mode of transport on the Helsinki-Tallinn route because general cargo is the main commodity on the route. IMO’s sulphur regula-tions and the changes in the structure of the Finnish industry may create prerequisites for rail road transport in the hinterland connections of Finland. The twin-city model has found to increase economical activity and well-being. The similar economical, social and cultural background of Finland and Estonia as well as the EU integration give good preconditions to create a twin-city of Helsinki and Tallinn. The relatively long distance between Helsinki and Tallinn is challenging. Therefore, good transport infrastructure and functioning connections are required to form a twin-city of Helsinki and Tallinn. The connections between these cities can be considered also in broader perspective than only from the viewpoint of the twin-city concept. New markets areas have been emerged in Europe due to collapse of planned economy and integration of Europe. Also the transport routes to the markets are changing. The Hel-sinki-Tallinn sea route can be considered as a fast route to the new markets in the Cen-tral and Eastern Europe. The Helsinki-Tallinn sea route is also a potential route to the Western European markets. This study provides an analysis of transport and cargo flows between Finland and Esto-nia for regional and local planners. The main purpose of the study is to clarify the pre-sent situation of the seaborne cargo flows on the Helsinki-Tallinn route and how the cargo flows will develop in the future. The study focuses on the following thematic enti-ties: the Finnish and Estonian seaborne transport system and cargo flows, the structure and volume of the cargo flows on the Helsinki-Tallinn route, the hinterland cargo flows on the Helsinki-Tallinn route and the transport methods used on the Helsinki-Tallinn route. The study was carried out as a desk research, a statistical analysis and an inter-view study during the spring–autumn 2011. The study reveals that during the period 2002–2010 the volume of the seaborne cargo traffic between Finland and Estonia has increased significantly while the trend of the trade volume between Finland and Estonia has remained nearly constant. This indicates that the route via Estonia is increasingly used in the Finnish foreign trade. Because the ports of Helsinki and Tallinn are the main ports in the cargo traffic between Finland and Estonia, the role of the Helsinki-Tallinn route as a sea leg in the hinterland connections of Finland has increased. The growth of the cargo volume on the Helsinki-Tallinn route was estimated to continue on the annual level of 10 % during the next couple of years. In the long run the growth of the cargo volumes depends on the economical and indus-trial development of the former Eastern European countries. If the IMO’s sulphur regu-lations will come in force, the Helsinki-Tallinn route will become one of the main routes also to the Western European markets, besides of the route via Sweden. The study also shows that the fast and reliable connections year round on the Helsinki-Tallinn route have made it possible for service and logistics companies to reconsider their logistics strategies in a new way in the both side of the Gulf of Finland. Anyway, the ropax concept is seen as the only economical profitable solution on the Helsinki-Tallinn route because cargo and passenger traffic are supporting each other. The trucks (vehicle combinations) will remain the main mode of transport on the Helsinki-Tallinn route because general cargo is the main commodity on the route. IMO’s sulphur regula-tions and the changes in the structure of the Finnish industry may create prerequisites for rail road transport in the hinterland connections of Finland.